Research on the spatial allocation of fundamental medical facilities utilizing multi-objective optimization–a case study on Tianjin - Sheng Zhang; Yongsheng Ma; Juan Ren; Hui Liu; Lei Cui; Zizhao Fan (Journal of Asian Architecture and Building Engineering)
Fundamental medical facilities, as a crucial component of public service infrastructure, contribute significantly to social welfare and serve as a basis for enhancing living standards and ensuring stable economic development. This paper developed a logical framework of “spatial accessibility-resource allocation-site optimization,” using Tianjin as a case study. Initially, we examined the existing configuration of fundamental medical facilities concerning spatial accessibility; subsequently, we assessed the rationality of medical resource distribution at the subdistrict level utilizing the Gini coefficient, Lorenz curve, and other mathematical and statistical analyses, and developed a supply-demand coupling coordination model to evaluate the interplay between facility supply and resident demand. Ultimately, we identified supply-lagged subdistricts, developed a multi-objective optimization site selection model, and employed the genetic algorithm (NSGA-II) within PyCharm to provide optimization recommendations and strategies. The study reveals significant deficiencies in the spatial arrangement of fundamental medical facilities in Tianjin regarding supply and demand alignment, exhibiting a gradient that diminishes from the city center to the periphery. Over half of the subdistricts experience a supply-demand disparity, with 76 subdistricts lagging in supply, constituting over 60% of the total. Thus, the efficiency of fundamental medical facility utilization dictates the degree of medical resource equalization.